Oxford handbook of pathology - Carton, James (Oxford : Oxford University Press, 2024)
An accessible and easy-to-use handbook which explains the pathology behind important and common diseases relevant to the whole range of medical and surgical specialties.
Previous edition: published as Oxford handbook of clinical pathology. 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on March 11, 2024).
Keywords: Pathology -- Handbooks, manuals, etc; Health and Wellbeing; Clinical & internal medicine